Cu-Zn isotope constraints on the provenance of air pollution in Central Europe: Using soluble and insoluble particles in snow and rime. (November 2016) - Novak, Martin; Sipkova, Adela; Chrastny, Vladislav; Stepanova, Marketa; Voldrichova, Petra; Veselovsky, Frantisek; Prechova, Eva; Blaha, Vladimir; Curik, Jan; Farkas, Juraj; Erbanova, Lucie; Bohdalkova, Leona; et al.
Abstract: Copper (Cu) and zinc (Zn) isotope ratios can be used to fingerprint sources and dispersion pathways of pollutants in the environment. Little is known, however, about the potential of δ 65 Cu and δ 66 Zn values in liquid and solid forms of atmospheric deposition to distinguish between geogenic, industrial, local and remote sources of these potentially toxic base metals. Here we present Cu-Zn deposition fluxes at 10 mountain-top sites in the Czech Republic, a region affected by extremely high industrial emission rates 25 years ago. Additionally, we monitored isotope composition of Cu and Zn in vertical and horizontal atmospheric deposition at two sites. We compared δ 65 Cu and δ 66 Zn values in snow and rime, extracted by diluted HNO3 and concentrated HF. Cu and Zn isotope signatures of industrial pollution sources were also determined. Cu and Zn deposition fluxes at all study sites were minute. The mean δ 65 Cu value of atmospheric deposition (−0.07‰) was higher than the mean δ 65 Cu value of pollution sources (−1.17‰). The variability in δ 65 Cu values of atmospheric deposition was lower, compared to the pollution sources. The mean δ 66 Zn value of atmospheric deposition (−0.09‰) was slightly higher than the mean δ 66 Zn value of pollution sources (−0.23‰). The variability in δ 66 Zn values of atmospheric deposition was indistinguishable from that of pollution sources. The largest isotope differences (0.35‰) were observed between the insoluble and soluble fractions of atmospheric deposition. These differences may result from different sources of Cu/Zn for each fraction. The difference in isotope composition of soluble and insoluble particles appears to be a promising tool for pollution provenance studies in Central Europe. Graphical abstract: Highlights: Cu and Zn isotope ratios in deposition were used to fingerprint pollution sources. The δ 65 Cu values of snow and rime were higher than those of pollution sources. The range of δ 65 Cu values of deposition was narrower compared to Cu sources. Soluble and insoluble Cu/Zn in rime and snow may originate from different sources. Abstract : The first data ever reported on Cu isotope composition of atmospheric deposition indicate that isotope fractionations may accompany the dispersion of pollutant Cu, similar to Zn.